Down Syndrome patients with COVID-19 pneumonia: A high-risk category for unfavourable outcome. (February 2021) - Vita, Serena; Di Bari, Virginia; Corpolongo, Angela; Goletti, Delia; Espinosa, Joaquin; Petracca, Sebastiano; Palmieri, Fabrizio; Nicastri, Emanuele; ,; Abbonizio,; Agrati, Chiara; Albarello, Fabrizio; et al.
Graphical abstract: Highlights: Pro-inflammatory factors play a central role in COVID-19 severity and mortality. Down Syndrome is characterised by immune dysregulation and respiratory infections. Down Syndrome patients with COVID-19 are at high risk of an unfavourable outcome. Abstract: We report two cases of Corona Virus Disease-19 (COVID-19) in patients with Down Syndrome (DS) and describe the identification, diagnosis, clinical course and management of the infection. Down Syndrome, which is caused by trisomy 21, is characterized by immune dysregulation, anatomical differences in the upper respiratory tract and higher rate of comorbidities. All these risk factors can contribute to more severe clinical presentations of COVID-19 in this population. It is essential to raise awareness of the clinical relevance of SARS-COV-2 infection in DS patients, as well as in other most vulnerable patients, in order to improve their management and treatment and to encourage vaccinating these individuals early, once a vaccination is available.